(untitled) (Research, Society and Development, 2021)
This study aimed to evaluate the perception of students from the Recife School of Dentistry (FOR) about the ENDO UPE application as a tool to support teaching-learning. The sample was composed of 83 students from the first to the tenth period. The online form consisted of 16 multiple-choice items and the results were tabulated by the platform itself in spreadsheets (via Google Sheets) and visualized in graphs. For this, the students had access to the survey invitation through a link on the online form, which was forwarded by the researcher through messages to the WhatsApp groups of the students’ classes. Frequency analysis of the variables was performed (mean and standard deviation, maximum and minimum values). SPSS 13.0 (IBM, Armonk, NY, USA) and Excel 2010 (Microsoft, Redmond, WA, USA) software were used. To verify the existence of associations, the chi-square and Fisher’s exact tests were used for categorical variables, considering p-value ≤ 0.05 for a 95% confidence interval as the significance level. The data collected show that the students of the Dentistry course of the Faculty of Dentistry of Recife (FOR) widely used the ENDO UPE application, recognizing it as an educational tool for the content of coronal opening of Endodontics.